Multimodal metaphtonymy in internet memes: A response to Donald Trump’s mug shot on X (formerly twitter) as a case study - Meleshchenko, Olga (Cognition, Communication, Discourse, 2024)
This study examines multimodal metaphtonymy in memes responding to Trump’s 2023 mugshot post on his X (formerly Twitter) account, @realDonaldTrump. The author employs the methodological tools of the conceptual (multimodal) metaphor and metonymy theory to identify patterns of interaction between metaphor and metonymy in these memes. The results reveal three types of multimodal metaphtonymy: metaphtonymy with a metonymy incorporated into either the metaphoric source or target, metaphtonymy with a metonymy incorporated into both the metaphoric source and target, and metaphtonymy with a metonymic chain structuring the metaphoric source. The metaphoric target domain of these metaphtonymies is identified as TRUMP-US PRESIDENT, reflecting Trump’s status as the 45th US President, a political leader, and a candidate for the 2024 US presidency within X platform. The study provides an in-depth analysis of each identified type of multimodal metaphtonymy instantiated by metaphorical portrayals of Trump as A CRIMINAL PSYCHOPATH, A TODDLER HAVING A TANTRUM, and A LIAR. The source domains of these metaphors map exclusively negative characteristics onto the TRUMP-US PRESIDENT target domain, with some features shared across several metaphoric source domains. The recurrent negative portrayals in memes create powerful and enduring images that shape public perception, contributing to a lasting tarnished image of Trump. These portrayals highlight the incongruity between Trump’s constructed image and the expectations of a US political leader, leading viewers to question his fitness for the presidency. The continuous negative portrayal undermines Trump’s credibility and reinforces the perception of his unfitness for leadership.